THE IMPORTANCE OF CRITICAL THINKING IN MODERN EDUCATION (World Bulletin of Social Sciences, 2024)
The current article aims at providing general information about critical thinking and its importance in modern education. The article also seeks to highlight the reasons why critical thinking is essential in modern education and suggests different strategies proven by experts and discusses benefits of critical thinking.
Keywords: Critical thinking skills; Creative Thinking; assumptions